Commutants of the Pommiez operator - Ivan H. Dimovski; Valentin Z. Hristov (International Journal of Mathematics and Mathematical Sciences)
The Pommiez operator (Δf)(z)=(f(z)−f(0))/z is considered in the space ℋ(G) of the holomorphic functions in an arbitrary finite Runge domain G. A new proof of a representation formula of Linchuk of the commutant of Δ in ℋ(G) is given. The main result is a representation formula of the commutant of the Pommiez operator in an arbitrary invariant hyperplane of ℋ(G). It uses an explicit convolution product for an arbitrary right inverse operator of Δ or of a perturbation Δ−λI of it. A relation between these two types of commutants is found.